The Protection Increase of Consumers Using Lending Institutions Under New Regulations Implemented by the Financial Markets Supervision Act and other Acts by the Amendment Dated 5th August 2015 - Mlostoń-Olszewska, Anna (Journal of Finance and Financial Law, 2016)
This publication concerns the regulations protecting consumers from excess charges when taking out loans from non-Bank Lending Institutions. The purpose of this publication is to discuss the new regulations implemented with the Financial Markets Supervision Act and other Acts by the Amendment dated 5th August 2015 concerning consumer credit and evaluate their effectiveness in improving consumer protection. It compares the new regulations to those used beforehand and critically analyses the new solutions. The publication proves that the new consumer protection model should increase consumer security.